2013
DOI: 10.1161/atvbaha.113.302054
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of Bone Morphogenetic Protein Receptor Axis During HIV-1 and Cocaine-Mediated Pulmonary Smooth Muscle Hyperplasia

Abstract: Objective Our previous findings support an additive effect of cocaine to HIV-infection in the development of pulmonary arteriopathy through enhanced proliferation of human pulmonary smooth muscle cells. We now examined the role of anti-proliferative bone morphogenetic protein receptor (BMPR) axis in HIV-protein and cocaine mediated pulmonary smooth muscle hyperplasia. Approach and Results Stimulation of BMPR axis resulted in attenuation of synergistic increase in the proliferation of human pulmonary arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(85 citation statements)
references
References 32 publications
10
75
0
Order By: Relevance
“…The present study contributes toward understanding our previous, consistent findings showing enhanced pulmonary vascular dysfunction in IVDUs infected with HIV compared with uninfected non-drug users or uninfected IVDUs (10,11,28,37). Here, we add new significant mechanistic details to support our earlier observation of uncontrolled proliferation of pulmonary SMCs associated with vascular remodeling in the presence of HIV proteins and illicit drugs.…”
Section: Discussionsupporting
confidence: 81%
“…The present study contributes toward understanding our previous, consistent findings showing enhanced pulmonary vascular dysfunction in IVDUs infected with HIV compared with uninfected non-drug users or uninfected IVDUs (10,11,28,37). Here, we add new significant mechanistic details to support our earlier observation of uncontrolled proliferation of pulmonary SMCs associated with vascular remodeling in the presence of HIV proteins and illicit drugs.…”
Section: Discussionsupporting
confidence: 81%
“…Quantitative RT-PCR was performed for checking the expression of ULK1, BECN1, ATG5, ATG7 and MAP1LC3B using SYBR green reagent as mentioned in our previous publications. 8 …”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…[4][5][6][7] Our previous findings consistently suggest augmentation of pulmonary arteriopathy and endothelial dysfunction in HIV-infected IVDUs (mainly opioids and/or cocaine abusers) compared to HIV-infected nondrug users or uninfected IVDUs. [8][9][10][11] Our previous study on lung tissues from simian immunodeficiency virus (SIV)-infected macaques exposed to morphine, an opioid (VM group), demonstrates significant pulmonary vascular remodeling including the presence of earlyand advanced-stage complex (plexiform) lesions when compared with either the SIV-infected (V group) or morphinetreated uninfected (M group) macaques. 10 Furthermore, the pulmonary endothelial cells (pECs) lining the vessels showing medial hypertrophy or initial stage intimal lesions in lung sections from VM macaques demonstrated an increase in positivity for both TUNEL (apoptosis marker) and MKI67 (proliferation marker).…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al 22 demonstrated the potential therapeutic use of the soluble Jagged1 because it not only inhibits proliferation of pulmonary VSMCs but also restores VSMCs phenotype from the dedifferentiated to the differentiated state through interference with Notch-Herp2 signaling. Finally, Dalvi et al 23 showed that simultaneous exposure of pulmonary VSMCs to viral proteins and cocaine exacerbates…”
Section: Vsmcs For Vascular Functionmentioning
confidence: 99%